TOWARD A BORDERLESS AFRICA: LEGAL AND POLICY FRAMEWORKS FOR IMPLEMENTING A PAN-AFRICAN FREE VISA REGIME TO REDUCE IRREGULAR MIGRATION AND PROMOTE YOUTH EMPOWERMENT - Thomas Sheku Marah (Journal of Governance and Public Administration, 2025)
Africa, the continent of so many cultures, so much potential; of even more borders and immigration policies, is in large part still a patchwork of disjointed countries lacking the free movement of people and goods across the whole continent. This paper analyzes the legal and policy principles of a continental free visa regime as part of the African Union’s Agenda 2063. It critically analyzes the implications of such integration for curbing irregular migration, harnessing the potential of African youth, and contributing to socio-economic development. Examining both the challenges and opportunities that exist for fostering continental unity through mobility, the study draws from primary legal instruments (such as the African Continental Free Trade Area (AfCFTA) and the Protocol on Free Movement of Persons). Employing a qualitative methodology bolstered by extensive literature and institutional reports, the paper demonstrates how, despite challenges of political will and security concerns, a harmonized visa policy is a viable solution that could decrease the risks of youth migration, promote economic independence, and strengthen African identity. The study concludes that a borderless Africa is attainable if policies are enhanced, cooperation by regional actors increased, and parties involved are engaged appropriately.